Promote Internally or Hire Externally? The Role of Gift Exchange and Performance Measurement Precision - CHAN, ERIC W.; LILL, JEREMY B.; MAAS, VICTOR S. (Journal of Accounting Research, 2023)
ABSTRACT Managers often face the choice between promoting an internal employee and hiring an external candidate. Using an interactive experiment, we examine the drivers of managers’ promote/hire decisions and internal employees’ behavior before and after those decisions. Consistent with gift exchange theory, we find that employees exert costly effort to increase the chance of being promoted, and they raise their effort level as the promote/hire decision becomes imminent. Managers respond by promoting those who exert high effort, despite employees’ inferior ability compared to external candidates. Results suggest that managers view employees’ past effort as both a gift to reciprocate and a signal of their future effort. Moreover, we find that managers are more likely to promote internally rather than hire externally under a less precise performance measurement system, and this result is driven by managers who observe low employee output. Finally, we find that total effort is significantly higher when managers promote internally versus hire externally.